Green Banking Dislocure Index: Unlocking Profitability Potential in Indonesia’s Islamic Commercial Banking - Hunafaa Al Qudsy, Naahilah; Haryadi, Imam; Prasetyo, Bangun Luhur (El-Barka Journal of Islamic Economics and Business, 2025)
Green banking, which emphasizes sustainability and environmentally responsible financing, has attracted significant global attention, yet its adoption faces challenges, particularly in emerging economies such as Indonesia. This study examines the impact of green banking on the profitability of Islamic commercial banks in Indonesia. This research utilizes secondary data sourced from the Financial Services Authority and annual reports of nine Islamic commercial banks in Indonesia, spanning the 2019-2022 period. Profitability is measured using Return on Assets (ROA), while the Green Banking Disclosure Index (GDBI) is employed to assess the extent of green banking implementation. The findings suggest that while green banking initiatives contribute to long-term sustainability, they do not exhibit a significant short-term impact on profitability. In contrast, the number of ATM units has a positive and statistically significant effect on profitability, primarily driven by increased fee-based income. The research advocates for enhancing green banking practices, particularly in the areas of carbon emissions management and waste recycling, and recommends that regulatory bodies strengthen policies to incentivize the adoption of environmentally sustainable banking practices. Additionally, improving sustainability reporting is essential for aligning with global sustainability objectives and fostering long-term profitability.